Whole-genome sequence of a stenotrophomonas maltophilia isolate from tap water in an intensive care unit - Zainulabid, Ummu Afeera; Shing, Wei Siew; Musa, Siti Munirah; Soffian, Sharmeen Nellisa; Periyasamy, Petrick; Ahmad, Hajar Fauzan (American Society for Microbiology, 2023)
Here, we present a 4,508,936-bp complete genome sequence of Stenotrophomonas maltophilia strain HW002Y, which was isolated from the tap water in an intensive care unit at Sultan Ahmad Shah Medical Centre at the International Islamic University of Malaysia (Kuantan, Pahang, Malaysia). Sequencing was performed using a Nanopore Flongle flow cell.